Emma [videorecording (DVD)] - Taylor-Joy, Anya, 1996-; Flynn, Johnny; O'Connor, Josh; Austen, Jane, 1775-1817 (Universal Pictures Home Entertainment, 2020)
Handsome, clever, and rich, Emma Woodhouse is a restless queen bee without rivals in her sleepy little town. In this glittering satire of social class and the pain of growing up, Emma must adventure through misguided matches and romantic missteps to find the love that has been there all along.